2018
DOI: 10.1177/0741088318786236
|View full text |Cite
|
Sign up to set email alerts
|

What Do Proofreaders of Student Writing Do to a Master’s Essay? Differing Interventions, Worrying Findings

Abstract: There has been much interest recently in researching the changes editors, supervisors, and other language brokers make to the writing of L2 researchers who are attempting to publish in English. However, studies focused on the pre-submission proofreading of students' university essays are rarer. In this study of student proofreading, 14 UK university proofreaders all proofread the same authentic, low quality master's essay written by an L2 speaker of English to enable a comparison of interventions.Proofreaders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…The current research incorporated these methodological suggestions. As in Harwood et al's work, ethics again emerged as a major theme in the present dataset, and, having elsewhere provided a detailed quantitative analysis of the frequency of corrections and comments they made (Harwood 2018), I focus in this article on the theme of ethics, and on the following research questions in particular:…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The current research incorporated these methodological suggestions. As in Harwood et al's work, ethics again emerged as a major theme in the present dataset, and, having elsewhere provided a detailed quantitative analysis of the frequency of corrections and comments they made (Harwood 2018), I focus in this article on the theme of ethics, and on the following research questions in particular:…”
Section: Introductionmentioning
confidence: 86%
“…Four methods were used to collect data: (i) a proofreader profile questionnaire; (ii) text analysis of the interventions informants made while proofreading an authentic master's-level essay written by a Chinese learner studying applied linguistics, which had been awarded a bare pass mark of 50; (iii) a talk aloud task, proofreaders explaining aloud what they were doing and why as they proofread; and (iv) a post-proofreading interview. In the method section of Harwood (2018), I provide a detailed description of each instrument, and in what follows, I focus particularly on how ethical issues were explored and uncovered.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, not all students are able to write at the level that their professors expect. Moreover, many studies have found that the errors in the students' assignments may affect their grades, whether positively or negatively (Harwood, 2018). Therefore, students are encouraged by their professors to carefully proofread their papers before submission.…”
Section: Introductionmentioning
confidence: 99%